(3GdeYQaI GdJGQjNjI ddfbO GdYQHj GdbOje (B/s - (3Jhajb, eLOj CMeOs ((3eUQ (B:s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ ,s, 2000)
(3JNJda GdeYQaI GdJGQjNjI ddfbO GdYQHj GdbOje Yf GdeYQaI GdJGQjNjI aj GdfbO GdYQHj GdbOje aGdehVhY GdKGfj jbhe Ydj GdSDGd (B: (3cja cGf GdfGbO GdbOje jYQa GdJGQjN$1 (3? h GdehVhY GdGhd jbhe Ydj GdSDGd(B: (3cja fYQa fMf JGQjN GdfbO GdYQHj GdbOje? h gPG gh GdSDGd GdPj jKjQg YPG GdcJGHs
Keywords: (3GdfbO GdYQHj GdbOjes; (3JGQjNs